HISTORY OF CONSTRUCTION IN BATAVIA DURING THE VOC PERIOD AS A FACTOR IN THE DEVELOPMENT OF ARCHITECTURE IN INDONESIA : Sejarah Pembangunan Batavia Sebagai Faktor Perkembangan Arsitektur di Indonesia - Meva Wulandari; Annisa Cikal Destiana; Najmia Khairani (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Architecture is an art and science that includes functional, aesthetic, cultural, social, and philosophical values. In the archipelago, architecture has long developed and reflects the influence of local culture, religion, and environment. The arrival of Westerners, especially the Dutch through the VOC, had a major impact on local architecture, creating acculturation between European styles and Nusantara traditions. Batavia Old Town, as the center of Dutch colonial administration, is a clear example of this acculturation. This research uses the architectural historiography method to analyze the history, structure, and influence of Batavia's colonial architecture on the development of the Nusantara's infrastructure. The results show that colonial architectural styles in Batavia, such as the use of local materials and adaptation to the tropical climate, resulted in a distinctive “Indies Vernacular” style. The structure of Batavia city, including its canals and spatial layout, reflects both colonial dominance and heritage that shaped Indonesian architectural identity. In addition, Batavia's Dutch canals have also been implicated in a record of functional failure due to incompatibility with local conditions. This research provides insights into the role of colonial architecture in shaping the infrastructure and urban development of the archipelago.